(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Production management plays a pivotal role in enhancing organizational efficiency and competitiveness in the contemporary industrial landscape. This paper explores the theoretical underpinnings and practical applications of production management. It delves into classical and modern theories, such as scientific management, systems theory, lean production, and total quality management. Furthermore, it analyzes practical strategies adopted in various industries to improve productivity, reduce waste, and ensure quality. The study highlights the evolving nature of production systems and suggests integrated approaches for aligning theory with current industrial practices. Findings indicate that a flexible yet systematic application of theoretical principles in real-world scenarios results in sustainable operational success.